COVID-19 in hospitalized infants aged under 3 months: multi-center experiences across Turkey - CANİZCİ ERDEMLİ, PINAR (My University, 2023)
To investigate coronavirus disease 2019 (COVID-19) in infants aged 0 to 3 months because there is currently a significant gap in the literature on the subject. A cross-sectional study was conducted with the involvement of 19 medical centers across Turkey and 570 infants. The majority of the patients were male (58.2%), and the three most common symptoms were fever (78.2%), cough (44.6%), and feeding intolerance (39.9%). The results showed that a small percentage of infants had positive blood (0.9%) or urine cultures (10.2%). Most infants presented with fever (78.2%). Children without underlying conditions (UCs) had mostly a complicated respiratory course and a normal chest radiography. Significant more positive urine culture rates were observed in infants with fever. A higher incidence of respiratory support requirements and abnormal chest findings were seen in infants with chronic conditions. These infants also had a longer hospital stay than those without chronic conditions. Conclusions: Our study discloses the clinical observations and accompanying bacterial infections found in infants aged under 3 months with COVID-19. These findings can shed light on COVID-19 in infancy for physicians because there is limited clinical evidence available. What is Known: • COVID-19 in infants and older children has been seen more mildly than in adults. • The most common symptoms of COVID-19 in infants are fever and cough, as in older children and adults. COVID-19 should be one of the differential diagnoses in infants with fever. What is New: • Although most infants under three months had fever, the clinical course was uneventful and respiratory complications were rarely observed in healthy children. • Infants with underlying conditions had more frequent respiratory support and abnormal chest radiography and stayed longer in the hospital.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics, Perinatology and Child Health; Breastfeeding; Children; Clinical presentation; COVID-19; Infants; Neonates